2022
DOI: 10.3390/ijms23169191
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Maternal Age Impairs Uterine Artery Adaptations to Pregnancy in Rats

Abstract: Advanced maternal age (≥35 years) is associated with pregnancy complications. Aging impairs vascular reactivity and increases vascular stiffness. We hypothesized that uterine artery adaptations to pregnancy are impaired with advanced age. Uterine arteries of nonpregnant and pregnant (gestational day 20) young (4 months) and aged (9 months; ~35 years in humans) Sprague-Dawley rats were isolated. Functional (myogenic tone, n = 6–10/group) and mechanical (circumferential stress-strain, n = 10–24/group) properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This represents a reduced maximum capacity for blood carrying capacity and potentially less ability to compensate for impaired vascular function when needed. Previously, using a pregnant rat model for advanced maternal age, we observed reduced circumferential strain in the uterine arteries of aged pregnant (vs. younger pregnant) rats at gestational day 20 (term = 22) [ 8 ]. In the rat model, we did not observe a difference in collagen:elastin ratio in arteries from pregnant rats of different age groups; however, during the present study, we observed that arteries from women of advanced maternal age had a greater collagen:elastin ratio compared with arteries from younger women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This represents a reduced maximum capacity for blood carrying capacity and potentially less ability to compensate for impaired vascular function when needed. Previously, using a pregnant rat model for advanced maternal age, we observed reduced circumferential strain in the uterine arteries of aged pregnant (vs. younger pregnant) rats at gestational day 20 (term = 22) [ 8 ]. In the rat model, we did not observe a difference in collagen:elastin ratio in arteries from pregnant rats of different age groups; however, during the present study, we observed that arteries from women of advanced maternal age had a greater collagen:elastin ratio compared with arteries from younger women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our lab demonstrated that advanced maternal age in rats impairs both vascular function and structure. Uterine arteries from aged pregnant rats have altered circumferential stress–strain relationships, including less strain, compared with younger pregnant controls [ 8 ]. Decreased strain values, with a leftward shift of the passive circumferential stress–strain curve, indicate reduced compliance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These increased risks in advanced maternal age could be explained by reproductive ageing, including declined uterine function and damage to the blood and endocrine system [ 25 ]. Studies have also shown that older pregnancies are associated with uterine atherosclerosis, impaired uterine myometrial contractility, changes in blood volume, vascular endothelial injury, decreased oxytocin receptors, and insulin receptor dysfunction [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous preclinical study, these same authors reported that circumferential strain of uterine arteries isolated at the end of pregnancy was lower in aged pregnant rats compared with young pregnant rats. However, they found no differences in strain between young non-pregnant and aged non-pregnant rats, mediated by matrix metalloproteinase dysregulation of elastin and collagen and enhanced myogenic vascular tone, leading to reduced vascular compliance [ 24 , 25 ]. These data suggest that decreased elastin content and circumferential strain at term reflects cardiovascular maladaptation to pregnancy in AMA, rather than a baseline effect of aging.…”
Section: Commentarymentioning
confidence: 99%